PERGERAKAN DAN FASILITAS PEJALAN KAKI DI KAWASAN PERKOTAAN KABUPATEN SUMEDANG - , ATO YULIANTO, Prof. Ir. Bambang Hari Wibisono, MUP., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to examine the needs and perceptions of society in Urban Areas of Sumedang District of pedestrian movement and local government response to the needs and perceptions. The study was done by conducting personal interviews with pedestrians on the sidewalk of Prabu Geusan Ulun St. and Mayor Abdurachman St. and interviews with government officials associated with the movement of pedestrians. In addition to interviews conducted also observation of pedestrian facilities and pedestrian intensity itself at a different time and day. The data obtained are then analyzed using descriptive qualitative analysis method of Miles and Hiberman namely through the stages, data reduction, data display and data verification. The study found that the sidewalk of Prabu Geusan Ulun St. and Mayor Abdurachman St in the Sumedang urban community center is great importance and a need for people to walk activity. The need for people to walk is affected by short-distance destinations and takes a short time. Routine activities, such as the home to go to school, to work and sports to the park make up the majority of activities carried out by foot for health reasons and savings. The condition of sidewalks and amenities on Prabu Geusan Ulun St. and Mayor Abdurachman St, in terms of design meets the standards of the Public Works Department, but in terms of provision of facilities and functions are not adequate. Local Government as planners, implementers and supervisors and controllers are less concerned about local development and attention to pedestrian movement, citing budget constraints. The study recommends about how important the government to further facilitate and protect the rights of pedestrians. Budget shortfalls can be overcome by conducting cooperation with the private sector in the form of mutually beneficial cooperation and the need for a paradigm shift that saw the pavement not only as a complement to the beauty of the city but more as a means of society to indulge with a safe and comfortable environment to enjoy the city.